PERBEDAAN KEKUATAN GESER REPARASI GIGI TIRUAN CEKAT DENGAN RESIN KOMPOSIT HYBRID DAN FLOWABLE - , Sri Budi Barunawati, Prof. Dr. Haryo Mustiko D, MS, Sp Pros(K) ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Composite resin is a selected material for repairing the fixed partial denture of porcelain fused to metal (PFM) because of its good aesthetics and low manipulation. This research was aimed at identifying the difference of shear bond strength of composite resin on metal surface and porcelain of fixed partial denture by using different composite resins, namely hybrid composite resin and flowable composite resin. The research subjects were cylinders with 10 mm in diameter and 3 mm in height. The research involved two groups. The first group was research subjects with metal material of NiCr (Noritake, Japan) and the second group with porcelain material (Bricera, USA). Each of which was divided into two groups, comprising 10 repair subjects with hybrid composite Hybrid (Z100TM,, 3M ESPE, USA) and 10 repair subjects with flowable composite (Dyad flow, Kerr, USA). The surface of the subjects were roughned with wheel diamond bur and etched with 37% phosphate acid (ScotchbondTM, 3M ESPE, USA). They were then washed and dried, silane (Rely X TM Ceramic Primer, 3M ESPE, USA) and bonding (Adper TM Single Bond, 3M ESPE, USA) were applied. The surface was then coated with hybrid and flowable composite resins and light-cured for 40 seconds. The research subjects were immersed in distilled water and put into the incubator at temperature of 37oC for 7 days. The shear bond strength test was conducted using the Universal Testing Machine. Data were analyzed using t-test for each metal and porcelain groups. The research result showed that there were differences of shear bond strength of repair between hybrid and flowable composite resins. The result of t-test indicated significant difference on metal surface (p<0.05) and on porcelain surface (p<0.05). The conclusion of this research is that shear bond strength of repair on metal surface and porcelain surface using hybrid composite resin has higher than that of flowable composite resins. The repair with hybrid composite resin using silane and bonding has higher shear bond strength than that of flowable composite resin which does not use additional application of silane and bonding.